Effect observation of 2% chlorhexidine gluconate solution wet compress in the treatment of PICC-related phlebitis and related nursing measures: A case report (2%葡萄糖酸氯己定醇湿敷治疗PICC所致静脉炎1例的护理体会) - MA Huigai (马会改); LI Ye (李野); TANG Ling (唐玲); E Haiyan (鄂海燕); BAI Yu (白羽) (中西医结合护理)
The peripherally inserted central catheter (PICC) is commonly used in the clinical setting, and PICC-related phlebitis is of great concern among doctors and nurses. This paper summarized the effect observation of 2% chlorhexidine gluconate solution wet compress in the treatment of PICC-related phlebitis and related nursing measures. The 2% chlorhexidine gluconate solution with characteristics of good antibacterial effect and less skin irritation is effective to relieve the syndrome of PICC-related phlebitis. (经外周静脉置入中心静脉导管(PICC)在临床应用广泛, PICC相关性静脉炎的防治是医护人员关注的重点问题。本文总结1例2%葡萄糖酸氯己定醇湿敷治疗PICC所致静脉炎的护理经验, 2%葡萄糖酸氯己定醇抗菌效果好、对皮肤刺激小等优点, 能有效改善静脉炎症状。)